Climate change and mental health research methods, gaps, and priorities: a scoping review. Issue 3 (March 2022) - Hwong, Alison R; Wang, Margaret; Khan, Hammad; Chagwedera, D Nyasha; Grzenda, Adrienne; Doty, Benjamin; Benton, Tami; Alpert, Jonathan; Clarke, Diana; Compton, Wilson M
Summary: Research on climate change and mental health is a new but rapidly growing field. To summarise key advances and gaps in the current state of climate change and mental health studies, we conducted a scoping review that comprehensively examined research methodologies using large-scale datasets. We identified 56 eligible articles published in Embase, PubMed, PsycInfo, and Web of Science between Jan 1, 2000, and Aug 9, 2020. The primary data collection method used was surveys, which focused on self-reported mental health effects due to acute and subacute climate events. Other approaches used administrative health records to study the effect of environmental temperature on hospital admissions for mental health conditions, and national vital statistics to assess the relationship between environmental temperature and suicide rates with regression analyses. Our work highlights the need to link population-based mental health outcome databases to weather data for causal inference. Collaborations between mental health providers and data scientists can guide the formation of clinically relevant research questions on climate change.